Sin taxes and self-control - Renke Schmacker; Sinne Smed (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
"Sin taxes" are high on the political agenda in the global fight against obesity. According to theory, they are welfare improving if consumers with low self-control are at least as price responsive as consumers with high self-control, even in the absence of externalities. In this paper, we investigate if consumers with low and high self-control react differently to sin tax variation. For identification, we exploit two sets of sin tax reforms in Denmark: first, the increase of the soft drink tax in 2012 and its repeal in 2014 and, second, the fat tax introduction in 2011 and its repeal in 2013. We assess the purchase response empirically using a detailed homescan household panel. Our unique dataset comprises a survey measure of self-control linked to the panelists, which we use to divide the sample into consumers with low and high levels of self-control. We find that consumers with low self-control reduce purchases less strongly than consumers with high self-control when taxes go up, but increase purchases to a similar extent when taxes go down. Hence, we document an asymmetry in the responsiveness to increasing and decreasing prices. We find empirical and theoretical support that habit formation shapes the differential response by self-control. The results suggest that price instruments are not an effective tool for targeting self-control problems.
Keywords: H20; D12; I18; 330; self-control; soft drink tax; fat tax; sin tax; internality